2019
DOI: 10.3390/jcm8070958
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Doripenem in the Treatment of Acute Bacterial Infections—A Systemic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: This study aims to assess the efficacy and safety of doripenem on treating patients with acute bacterial infections. The Pubmed, Embase, and Cochrane databases were searched up to April 2019. Only randomized clinical trials comparing doripenem and other comparators for the treatment of acute bacterial infection were included. The primary outcome was the clinical success rate and the secondary outcomes were microbiological eradication rate and risk of adverse events. Eight randomized controlled trials (RCTs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…In terms of PA pneumonia, doripenem has a microbiological cure rate, a clinical cure rate, and an all-cause mortality similar to those of comparator antimicrobial agents for the treatment of PA pneumonia. There were only two meta-analyses reported in the literature that explored doripenem therapy for bacterial infections [ 23 , 24 ]. The two meta-analyses also reported that doripenem had a microbiological cure rate, a clinical cure rate, and an all-cause mortality similar to those of comparator antimicrobial agent therapies for bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of PA pneumonia, doripenem has a microbiological cure rate, a clinical cure rate, and an all-cause mortality similar to those of comparator antimicrobial agents for the treatment of PA pneumonia. There were only two meta-analyses reported in the literature that explored doripenem therapy for bacterial infections [ 23 , 24 ]. The two meta-analyses also reported that doripenem had a microbiological cure rate, a clinical cure rate, and an all-cause mortality similar to those of comparator antimicrobial agent therapies for bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicamente é aprovado para uso em infecção intra-abdominal complicada (IAI), infecção complicada do trato urinário (ITUc) e pielonefrite/pneumonia associadas a assistência da saúde (PAH). Um estudo recentemente demonstrou que esse antimicrobiano foi duas vezes mais potente in vitro quando comparado ao Imipenem e meropenem (LAI et al, 2019).…”
Section: Doripenemunclassified
“…By contrast with the study by Kollef and colleagues, 2 which was unable to show non-inferiority for doripenem, the other two studies 3,4 compared doripenem with comparators over a similar treatment duration and reported noninferiority for doripenem. Doripenem was most commonly used for treating pneumonia in a surveillance study, 5 and a meta-analysis up to April, 2019, 6 showed that doripenem was non-inferior to comparators in the treatment of nosocomial pneumonia and ventilator-associated pneumonia. Therefore, we wonder whether doripenem can achieve noninferior efficacy if it can be used for the same duration as the comparator.…”
Section: Doripenem For Treating Nosocomial Pneumonia and Ventilator-amentioning
confidence: 99%
“…Mechanically ventilated patients are generally critically ill, and thus might have augmented renal clearance or other factors affecting antimicrobial pharmacokinetics. 6 This can lead to insufficient drug concentrations at the infection site, compounded by the greater prevalence of pathogens with higher minimum inhibitory concentrations in the intensivecare unit. 6,7 Under-dosing, especially in ventilated patients, has been suggested as a contributing factor in several trials unable to show…”
mentioning
confidence: 99%